Combination of Sulfuric Acid (H2SO4) and Aquadest to Detect Goat Pregnancy - Nur Ifa Rohmayanti; Ayu Wulandari; Muhammad Rifai; H. Hastuti (Chalaza Journal of Animal Husbandry, 2018)
Pregnancy detection is an essential thing to do after cattle are mated. In general, early pregnancy detection is needed regarding identifying animals that are not pregnant immediately after natural mate or artificial mate, so that production time is lost because infertility can be suppressed by proper handling such as livestock must be sold or dialing (cut). It is aimed at reducing costs for breeding, programs and helping livestock management economically. Many methods can be used for pregnancy detection depending on the species, age of pregnancy, cost, accuracy, and speed of diagnosis. The purpose of each method used in pregnancy examinations is to determine the pregnancy status with 100% accuracy, especially in the Watubangga and Toari areas, which breeders are still applying traditional methods, which this detection method can reduce costs, time and effort, especially this detection method relatively cheap and easy to do.